State of the Art Review on Prescriptive & Performance Based Approaches for Concrete Durability - Ali, Salid; Naganathan, Sivakumar; B, Mahalingam (International Journal of Sustainable Construction Engineering and Technology, 2021)
Durability is a crucial and important requirement for concrete structures. A durable concrete not only leads to sustainability but serve for longer period of time without much repair and maintenance. The Concrete has been studied under various exposure conditions as stated in relevant standards but no significant attention is given for the in service performance of the concrete. In the last few decades, many researchers investigated the causes of structures deterioration and suggested various solutions to tackle the durability issues which are mainly adopting of performance-based specifications rather than prescriptive. In this paper, the previous findings on concrete durability are reviewed. The studies on the durability problems are highlighted along with prescriptive and performance-based approaches and test methods. The effects on service life of the structures along with the solution are reviewed.